Nutrient Intakes among Jordanian Adolescents Based on Gender and Body Mass Index - ALjaraedah, Thana’ Y.; Tayyem, Reema F.; Takruri, Hamed R. (International Journal of Child Health and Nutrition, 2020)
Background: This study was conducted to examine the dietary intakes of macro- and micronutrients for a Jordanian adolescents based on gender and compare their intake to the Dietary Recommended Intakes (DRIs). Methods: A sample of 398 male and female adolescents, aged 14-18 years, were recruited from private and public schools using convenience sampling. Socio-demographic questionnaire and 3-days food record were self-reported. Bodyweight and height were measured and body mass index (BMI) was calculated for all participants. Results: There were no significant differences between male and female adolescents regarding the intake of micro and macronutrients except for protein, insoluble fibre, saturated fat, cholesterol, omega-6, vitamin E and calcium. The intake of insoluble fibre (g/day), omega-6(g/day), and vitamin E (mg/day) was significantly higher in female adolescents (3.1±0.1, 5.6±0.5, and 3.1±0.3, respectively, P≤0.05) compared to male adolescents (2.9±0.1, 5.1±0.4, and 2.5±0.2, respectively, P≤0.05). On the other hand, the intakes of protein (g/day), saturated fat (g/day), cholesterol (mg/day), calcium (mg/day) were significantly higher in male adolescents (90.1±2.3, 31.7±1.0, 339.2±18.3, and 651.5±27.8) as compared with female adolescents (79.2±2.1, 29.2±1.2, 263.6±14.9, and 555.2±21.7) (P≤ 0.05). Comparing of the adolescents’ nutrients intake to the DRIs, many nutrients were found to be below or above the recommendations. Conclusion: The study findings highlighted that there is an urgent need to establish a plan of action to combat malnutrition among adolescents in Jordan.